The Impact of Sport and Physical Activity on Urinary Incontinence: Does Exercise Act as a Protective Factor or Increase Risk? - Ptak, Anita; Szyc, Michał (Quality in Sport, 2024)
Introduction: Urinary incontinence is a health problem which affects women more often. The condition manifests itself as uncontrolled urine leakage. A basic distinction is made between stress urinary incontinence (SUI), urgency urinary incontinence (UUI), and mixed urinary incontinence (MUI). Physical activity is commonly used in the treatment of UI. Interestingly, numerous studies show that athletes and especially female athletes are more likely to develop UI. In this study, we will try to answer the question of whether sport and physical activity have a protective effect or are a risk factor for the development of UI. In this review, we will focus on sports and physical activity that does not directly target pelvic floor muscle training. Aim of the study: A review of the literature on the impact of sport and physical activity on the prevalence of urinary incontinence in both sexes in different age groups and different health and fitness statuses Materials and methods: A review of the recent literature available in PubMed and Google Scholar databases was conducted, using keywords such as ‘urinary incontinence’, ‘stress urinary incontinence’, ‘prostatectomy”. This review was enriched by urological guidelines on urinary incontinence. Conclusion: Urinary incontinence is a common ailment, especially among women. Particularly at risk are those who participate in high-intensity sports and do prolonged training, performing exercises such as jumping and sprinting. On the other hand, limited physical mobility is also a risk factor for incontinence. Keeping active in seniors can reduce symptoms. Exercises with positive effects include Pilates, which has very good efficacy in men after total prostatectomy surgery. Physical activity may also help to reduce body weight, as obesity is a recognised risk factor for urinary incontinence. Further research into the therapeutic use of exercises such as yoga and Pilates is warranted and may help treat patients with incontinence.